Early Diagnosis of Mycoplasma pneumoniae in Children: Simultaneous Amplification and Testing (SAT) Is the Key - Li, Jieqiong; Sun, Lin; Wu, Xirong; Guo, Yan; Jiao, Weiwei; Xiao, Jing; Xu, Baoping; Shen, Adong (Frontiers in Pediatrics, 2019)
Objective: Diagnosis of Mycoplasma pneumoniae (MP) pneumonia (MPP) in children has been hampered by difficulty in early diagnosis and disease progression monitoring. The simultaneous amplification and testing (SAT) has the potential for early diagnosis and progression monitoring of MP in children. Methods: A total of 1180 children (169 confirmed MPP, 641 probable MPP, 370 un-MPP) were included in the study. Sera and pharyngeal swab were collected for serological testing (Ab) and SAT detection respectively on admission. If the samples were negative for Ab, paired-Ab was further detected in 7 days later. After discharge, a following study was conducted in SAT positive children to analysis the correlation between SAT and disease progression. Results: Using the Ab result as a diagnostic standard, the sensitivity, specificity, positive predictive values (PPV) and negative predictive values (NPV) of SAT were 72.8%, 95.1%, 97.0% and 61.5%, respectively. SAT showed better diagnostic value in the MP confirmed group (sensitivity: 82.2%; NPV: 92.1%) and the short-course group (sensitivity: 81.0%; NPV: 81.3%). Good agreement was observed between the SAT and paired-Ab results (kappa value=0.79; P<0.001), although there was a lack of consistency between the SAT and single-Ab results on admission (kappa value=0.54, P<0.001). Besides, the time of SAT results turned negative closely matched the clinical recovery time (3.0±0.7 weeks vs. 3.1±0.5 weeks, r=0.501, P>0.05). Conclusion: SAT is a rapid, sensitive, and specific method for MP identification. It is an effective and valuable diagnostic tool for clinicians to detect MPP at the initial phase of infection and correlate with disease progression.